Determining the vulnerability of states in Nigeria to COVID-19 (2020)
The impact of the coronavirus disease 2019 (COVID-19) pandemic has been felt globally. However, against the backdrop of the uncertainties surrounding the pandemic, and the pronouncement of the World Health Organization that the virus may never go away, it has become pertinent for nations to identify and protect the most vulnerable of their citizens. This study determined the states with the highest vulnerability to the pandemic in Nigeria. The 2006 population data for each state of the federation was obtained from the National Population Commission (NPC) Nigeria, and was projected to the year 2020. Data on: Nigerians aged 60 years and older, the percentage population in the lowest and second wealth quantiles, percentage population without fixed handwashing and moderate handwashing facilities, and percentage population of male and female without exposure to mass media, were obtained from the 2018 Nigeria Demographic and Health Survey report. Prevalence rates of High Blood Pressure, Diabetes Mellitus, Cardiovascular Disease, and Asthma were extracted from literature. These were used to estimate a vulnerability score for each state of the federation and the Federal Capital Territory. Kebbi had the highest score (39.82), followed by Zamfara (39.27) and Sokoto (39.24), respectively. Osun (11.45), Abia (12.53), and Lagos (15.47), have the least scores, respectively. The most vulnerable geo-political zone was the Northwest, while the least vulnerable was the Southwest. Regression analysis was carried out to model the data. Appropriate steps should be taken to reduce likely mortalities due to high vulnerability to COVID-19 in the identified States.